Adoption Adaptation of the Terms of Economic Science and Enrichment of Indonesian Vocabulary - Kaharuddin (Cendekiawan Indonesia Timur, 2022)
This research aimed to know economics terms used every day in written media, electronic media, and verbal interaction. All the words be seen if Indonesian vocabularies develop. To catch some information about economics terms, the writer chooses the library method by observing and noting all terms of economics throughout media (written, electronic) and social interaction. What the writer analyzed, the writer caught 203 economics terms which used, but only 77 terms or 34.94 percent, usually used in communication every day. It pointed that economics contributed a lot to Indonesian vocabularies enrichment.